Effects of St and Re on propulsive performance of bionic oscillating caudal fin. (1st December 2020) - Liu, Peng; Wang, Siqi; Liu, Ranran; Shang, Zhiqiang
Abstract: Many fishes show an excellent swimming ability by agilely oscillating their fins, and the caudal fin is a main organ for a fish to propel itself. This propulsion mode provides inspiration to the design of biomimetic underwater vehicles. On this basis, we take an oscillating fin as our study subject and build a computational fluid dynamic model by mimicking the lunate caudal fin of tuna. Numerical simulations are performed to evaluate the effects of the Strouhal number ( St ) and Reynold number ( Re ) on the wake structure and hydrodynamic performance of the oscillating caudal fin. Navier-Stokes equations are used to solve the unsteady flow for the oscillating caudal fin, as well as the user-defined-function and dynamic mesh methods are applied to realize and track the instant locomotion, respectively. Then the validity and reliability of the numerical method are verified by experiments and convergence tests. Results show that the fish can obtain a larger instantaneous thrust force when the caudal fin flaps under a higher St but when its propulsive efficiency is mediocre or even worsens. This situation usually occurs during the escape or hunting actions of fish. Meanwhile, being in a turbulence flow, which corresponds to a larger Re, is helpful for the caudal fin to obtain a relatively higher thrust force and propulsive efficiency. Specially, a detailed analysis on the connection between the wake vortex topology, kinematics and force generation of the caudal fin is performed. Results suggests that the wake is dominated by one or two sets of complex vortex rings which convect at different oblique angles to the wake flow centerline. With various Re and St, the hydrodynamic performances of the caudal fin strongly depend on the flow dynamics underlying the force production, including the orientation, interconnection and dissipation rate of the vortex rings. Such as jet flows inducted by these vortex rings, play a critical role in the thrust force generation for an oscillating caudal fin. Highlights: An increasing St leads to larger thrust force and lower propulsive efficiency of caudal fin, but it is reversed for Re . The oscillating motions of caudal fin with a higher St usually occur when fish attempt to hunt or escape. Fluid inertial force and viscous force affect thrust and resistance of the caudal fin, respectively. Re affects the scale and dissipating rate of vortex rings, and St affects the appearance features of vortex system.